Estructura trófica de una comunidad de artrópodos epígeos, en un magueyal del Bolsón de Mapimí, Dgo., México (Desierto Chihuahuense) - Rivera García, Eduardo; Viggers Carrasco, Guadalupe (Instituto de Ecología, A.C., 1991)
This paper analizes the trophic structure of an surface active arthropod community in the Chihuahuan Desert (Mapimí Reserve, Durango, México). Trophic structure was determined on the basis of feeding and foraging habits of adutts. Differences in abundance and biomass diversity were found in two years for ail trophic levels considered (P <0.05). Eveness was similar for abundance and biomass during the 2 years for any trophic level considered. Community composition changed between 1987 and 1988 in all trophic levels faunistic composition similarity (familias recordad) between the two years was higher for omnivorous (75 %) than for fitophagous (55.1 %).